2000
DOI: 10.1097/00054725-200008000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Pseudomembranous Colitis in a Patient with Ulcerative Colitis

Abstract: The presence of toxic megacolon due to Clostridium difficile in patients with ulcerative colitis is a rare complication that may be suspected in patients with initial relapse who are on antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…7,10,11,16 Inflammatory bowel disease (IBD) and fulminant C difficile colitis, generally a topic of case reports, were prominent in our series. 21,22 Clinical and pathologic diagnoses were able to definitively attribute the acute colitic episode to C difficile, supporting literature that refutes an association between IBD exacerbation and C difficile infection. 23,24 Despite being well represented in our series, no patients with IBD were counted among the mortalities.…”
Section: Commentsupporting
confidence: 61%
“…7,10,11,16 Inflammatory bowel disease (IBD) and fulminant C difficile colitis, generally a topic of case reports, were prominent in our series. 21,22 Clinical and pathologic diagnoses were able to definitively attribute the acute colitic episode to C difficile, supporting literature that refutes an association between IBD exacerbation and C difficile infection. 23,24 Despite being well represented in our series, no patients with IBD were counted among the mortalities.…”
Section: Commentsupporting
confidence: 61%
“…5 Our review of the medical literature in PubMed between 1975 and 2009 revealed three cases of PMC complicating UC. [2][3][4] The details of all four reported cases, including the present case, are shown in Table 1. There were three men and one woman, and their mean age was 52.8 years.…”
Section: Discussionmentioning
confidence: 93%
“…Our literature search yielded only three similar cases. [2][3][4] Herein, we present a case of PMC complicating UC, along with a review of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that 14.1 % (16/113) of the samples were positive for CDAD; five were from the patients under immunosuppressive therapy and 11 were from the patients receiving no medication or treatment. García-Osogobio et al (2000) presented a case report of a 52-year-old male patient with ulcerative colitis that progressed to toxic PMC. This patient had been treated for amoebiasis with metronidazole but, after 2 weeks of recovery, the symptoms recurred.…”
Section: Jamaicamentioning
confidence: 99%